Understanding food insecurity among public university students - Law, Leh Shii; Baki, Roselan; Sulaiman, Norhasmah (Institut Penyelidikan Pembangunan Belia Malaysia, 2015)
This article aims to understand food insecurity among public university students. The informants were four university students (two males and two females), all of whom were selected purposively. Face-to-face interviews were conducted in accordance with an interview protocol so that the required information may be collected properly. This was crucial to ascertain and comprehend the contributing factors, coping strategies and consequences of such food insecurities. Interviews were audio-recorded and transcribed verbatim. In addition to that, thematic analysis was applied to identify the codes used to form themes. The conclusive findings showed that the sudden closure of cafeterias, financial problems, lack of personal transportation, low quality of food and time constraints were among the factors contributing to food insecurities. Coping strategies were applied to combat these, including purchasing food outside campus grounds, forcing down dissatisfying cafeteria and mini-mart meals, storing foodstuff, reducing meal portions, choosing cheaper foods, opting for cleaner cafeterias, requesting outside food from friends and skipping meals completely. Consequently, there were dire effects, such as anxiety, lack of energy, inability to focus during classes and falling ill. Therefore, the Malaysian Ministry of Education as well as the university authorities themselves should be made aware of the food insecurity problems faced by university students. Further study in the future with a larger number of students involved is recommended.